Pengaruh Pengembangan Wisata Kuliner dan Ekonomi Kreatif Terhadap Minat Berkunjung Wisatawan di Kota Berastagi - Barus, Nikolas Syahputra; Manalu, Darma; Simangunsong, Ridhon NB. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This research aims to determine the influence of culinary tourism and the creative economy on tourist interest in visiting the city of Berastagi. This research was conducted using quantitative methods. Data collection techniques using questionnaires. Based on hypothesis testing with the t test, the calculated t value for the culinary tourism variable is 2.166, where the value is > 1.986 from t table and the significant value for the culinary tourism variable is 0.01 < 0.05 (5%). In the creative economy variable, the tcount value is 2.220, where the value is > ttable 1.986 and the significant value in the creative economy variable is 0.03 < 0.05 (5%). So it can be concluded that culinary tourism and the creative economy have a positive and significant influence on tourists' interest in visiting the city of Berastagi. And the f test obtained a calculated f value of 9.855 where this value is > f table of 3.09. And the significant value is 0.000 < the significance level of 0.05. So it can be concluded that culinary tourism and the creative economy simultaneously have a positive and significant effect on tourists' interest in visiting.